Zoom : the challenge of scaling with COVID-19 on the horizon (A) - Isaacs, Andrew M., (SAGE Business. Cases., 2020)
In January 2020, when the first case of COVID-19 was confirmed in the United States, American business leaders were only beginning to understand the potential economic impact. Zoom Video Communications, Inc., headquartered in Silicon Valley, monitored the fast-moving virus, knowing it was in the eye of the storm. In its eight years, Zoom had managed rapid growth successfully; It was a unicorn who competed with industry players. Zoom had tackled four key challenges: inspiring a happy company culture, outmanoeuvring competitors, managing profitability, and solving security problems. But in February of 2020, had Zoom's past experience prepared the company to pivot, withstand, and perhaps even benefit from a looming outside, unexpected, global challenge of unknown proportions?